Strategic Implementation of Servant Leadership : Enhancing Effectiveness in Employee Engagement and Driving Organizational Performance - Deepak Kumar; Prof. (Dr) Rajni Saluja (International Journal of Scientific Research in Science and Technology, 2024)
This study examines the strategic effectiveness of servant leadership in fostering employee engagement and enhancing job performance, emphasizing its transformative potential within organizational settings. Servant leadership prioritizes the well-being, growth, and empowerment of employees, creating a supportive environment that aligns personal and organizational goals. By focusing on ethical behavior, empathy, and collaborative decision-making, servant leadership establishes a culture of trust and mutual respect, which drives both individual and collective success. Theoretical insights reveal that servant leadership significantly impacts key aspects of employee engagement, such as vigour, dedication, and enthusiasm for work. Employees led by servant leaders are more likely to feel valued, motivated, and committed to their roles, resulting in improved job satisfaction and productivity. Furthermore, servant leadership fosters psychological safety, enabling employees to innovate, take risks, and work collaboratively without fear of failure. These behaviours not only enhance individual job performance but also contribute to organizational resilience and adaptability. Strategically, the study identifies several approaches to enhance servant leadership effectiveness, including fostering open communication, providing personalized mentoring, and promoting a shared sense of accountability. By addressing employee needs holistically, servant leadership ensures a sustainable and inclusive workplace culture. This theoretical framework underscores servant leadership’s potential as a model for achieving long-term organizational excellence and employee fulfilment.
Keywords: Strategic Implementation; Servant Leadership; Employee Engagement; Performance